Pengaruh Kemampuan Berpikir Kritik dan Konsep Diri Terhadap Prestasi Belajar Matematika - Dona Katarina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2017)
The direct effect of the ability to think criticism of the concept of self-esteem, self-concept directly determine the effect of students' mathematics achievement and to determine the effect of indirect criticism of the ability to think mathematics achievement through student self-concept. Data analysis using descriptive statistical methods and testing techniques of data analysis requirements. The results showed: (1). there are a significant direct influence thinking skills of criticism and self-concept of the student mathematics achievement. (2). there is a significant direct influence thinking skills critique of mathematics achievement. (3). there is a significant direct effect on the achievement of self-concept study mathematics. (4) there is an indirect effect is not significant ability to think criticism of mathematics achievement through self-concept.